Knowledge, attitudes, and practices of lung cancer patients regarding nutritional management during chemotherapy - Cao, Jie; Xiang, Feng; Zhang, Jun; Tang, Yun; Hu, Min; Li, Fangfei (Frontiers in Nutrition, 2026)
ObjectiveMalnutrition is common in lung cancer patients receiving chemotherapy and contributes to treatment intolerance, poorer quality of life, and reduced survival, emphasizing the need for effective nutritional management. This study aims to investigate the knowledge, attitudes, and practices (KAP) related to nutritional management during chemotherapy among lung cancer patients.MethodsA cross-sectional survey was conducted at Chongqing University Cancer Hospital between May and July 2025. Patients with lung cancer were invited to complete a structured questionnaire to collect demographic data and evaluate KAP related to nutritional management during chemotherapy. The Nutritional Risk Screening 2002 score (NRS-2002) was used to identify individuals at risk of malnutrition.ResultsA total of 598 valid responses were collected. Most participants were male (57.4%). More than half of the patients (57.4%) had a history of chemotherapy, and 14.1% had an NRS-2002 score above 3, indicating nutritional risk. The mean scores for knowledge, attitude, and practice were 12.07 ± 4.69 (range: 0–20), 35.89 ± 4.98 (range: 9–45), and 23.28 ± 4.12 (range: 6–30), respectively. Structural equation modeling revealed that knowledge had significant direct effects on both attitude (β = 0.601, p = 0.011) and practice (β = 0.345, p = 0.006). Attitude also directly influenced practice (β = 0.558, p = 0.010). Additionally, knowledge exerted an indirect effect on practice through attitude (β = 0.335, p = 0.014).ConclusionPatients with lung cancer undergoing chemotherapy demonstrated limited knowledge but generally positive attitudes and moderate practices regarding nutritional management. Targeted educational interventions are warranted to enhance patients’ nutritional knowledge, which may further reinforce their attitudes and improve their self-management behaviors during chemotherapy.